Determinantes socioeconômicos da taxa de lesão autoprovocada não suicida nos estados brasileiros de 2010 a 2018: um estudo com dados em painel. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This study aims to identify que socio-economic determinants related to the nonsuicidal self-injury in the states of Brazil between 2010 and 2018 using the theory of the suicide rates’s socio-economic determinants as a basis. Nonsuicidal self-injury, or also self- harm, is one of the behaviors that define self-directed violence together with suicidal behavior, characterized as violence committed against oneself according to the World Health Organization. Literature on nonsuicidal self-injury comprises epidemiological, descriptive and characterization studies, with few studies based on econometric methodology. Suicide, however, has a vast literature of econometric studies on its socio-economic determinants and, considering its direct relationship with nonsuicidal self-injury, it was decided to use the literature on suicide as a basis for the study. As a methodology, the two-way Fixed Effects model was used for panel data after analyzing results from specification tests that helped decide the most appropriate estimation method. Three models, each with a distinct dependent variable, were estimated to observe whether socio-economic determinants have different impacts on total, male and female nonsuicidal self-injury rates. The results showed that the rates are highly influenced by the state GDP per capita, which was negative, by the fertility rate, which had positive coefficients, and by the Gini Index, which has an inverse relationship with the dependent variables. The female labor participation rate has a positive relationship in the three models, but it is significant only in relation to women. Finally, unemployment and divorce rates, with positive and negative coefficients respectively, did not show statistical significance for the model.
Keywords: Lesão autoprovocada não suicida; Violência autoprovocada; Determinantes socioeconômicos; Dados em painel; Efeitos fixos; Nonsuicidal self-injury; Self-directed violence; Socio-economic determinants; Panel data; Fixed effects; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA